Office endometrial sampling: a comparison between Endosampler and Karman cannula number 4 - Zutshi, Vijay; Gupta, Monika; Kaur, Panchampreet; Malik, Aarzoo; Zaheer, Sufian; Gambhir, Puneet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Endometrial aspiration biopsy is one of the primary steps in diagnostic evaluation of a women presenting with suspected endometrial pathology. The aim of present study was to compare specimen adequacy, ease of doing the procedure, patient comfort and cost effectiveness in office endometrial sampling by endosampler vs Karman cannula number 4. Methods: This was a prospective comparative study where 102 patients were included. In 50% of patients, endosampler was used and Karman cannula was used in the rest. All procedures were noted, analysed and done in outpatient department and various parameters like specimen adequacy, pain score, ease of doing the procedure were analysed and compared in both groups. Results: The mean age of the patients was 37.1(±10) years with comparable distribution in the two groups. The parity was comparable in both groups. Authors further analysed the data on the basis of operator experience. The mean score of ease of insertion based on the experience of residents of < 2 years and > 2 years was 3.1±1.48; 4.0±1.96 and 3.5±1.5; 3.7±2 in endosampler and Karman cannula group respectively. This difference was significant in the endosampler group (P: <0.001). The difference in pain score in two groups was not significant. The specimen obtained was adequate in 32 (62.7 %) patients of the endosampler group and in 39 (76.4 %) patients of the Karman cannula group. (p-0.07). Endosampler is five times costlier than Karman cannula. Conclusions: Karman cannula is a good and cost-effective sampling device for endometrial biopsy.